Answer:
![y = 3x - 6](https://tex.z-dn.net/?f=y%20%3D%203x%20-%206)
Step-by-step explanation:
A linear function has the following format:
![y = ax + b](https://tex.z-dn.net/?f=y%20%3D%20ax%20%2B%20b)
In which a is the slope(rate of change) and b is the y-intercept, that is, the value of y when x = 0.
Rate of change of 3
This means that ![a = 3](https://tex.z-dn.net/?f=a%20%3D%203)
So
![y = 3x + b](https://tex.z-dn.net/?f=y%20%3D%203x%20%2B%20b)
A solution at (6, 12).
This means that when x = 6, y = 12. So
![y = 3x + b](https://tex.z-dn.net/?f=y%20%3D%203x%20%2B%20b)
![12 = 3*6 + b](https://tex.z-dn.net/?f=12%20%3D%203%2A6%20%2B%20b)
![b = -6](https://tex.z-dn.net/?f=b%20%3D%20-6)
The linear function is:
![y = 3x - 6](https://tex.z-dn.net/?f=y%20%3D%203x%20-%206)
Answer: -x^3 - x^2 + 3x - 3
Glad I could help :D
Step-by-step explanation:
Answer:
The points for the given two linear equation as
= - 2 , - 6
= - 2 , 6
The graph so plotted as shown
Step-by-step explanation:
Given as :
The two linear equation are
y = 3 x ........A and
y = - x - 8 .........B
Solving equation A and B
Now, Put The value of y from eq A into eq B
So, 3 x = - x - 8
Or, 3 x + x = - 8
Or, 4 x = - 8
∴ x = ![\dfrac{-8}{4}](https://tex.z-dn.net/?f=%5Cdfrac%7B-8%7D%7B4%7D)
I.e x = - 2
Now , Put the value of x into eq A
∵ y = 3 x
∴ y = 3 × (-2)
I.e y = - 6
Again, Put the value of x into eq B
∵ y = - x - 8
∴ y = - 2 - (-8)
I.e y = 6
So, for x = - 2 , y = - 6
And for x = - 2 , y = 6
Hence , The points for the given two linear equation as
= - 2 , - 6
= - 2 , 6
The graph so plotted as shown . Answer
Answer:
4
Step-by-step explanation:
The Triangle Inequality Theorem states that the sum of any 2 sides of a triangle must be greater than the measure of the third side.
If you add 2 and 4, you will get 6. This is the right answer because the only answer that is incorrect is the 4th, it has to equal a minimum of 7, not 6.